FORMULASI FOUNDATION (ALAS BEDAK) DARI CANGKANG TELUR AYAM NEGRI - Supartini, Entin; Arief, Adilla Edi; Suharyani, Ine (STIKes Muhammadiyah Kuningan, 2023)
ABSTRACT Foundation (Compact Powder) is a decorative cosmetics (makeup) used in cosmetology as a base before sprayed powder. Foundation serves to disguise pale skin, make face powder more attached to the surface of the skin, and cover blemishes acne scars. Chicken’s egg shell contains carbonate calcium (CaCO3) at around 94%, also protein and vitamins. CaCO3 has a strength to revet and gives the radiant effect when face powders be used, so that egg shell are well suited as a base material foundation. Foundation is made in the form of a lotion product (liquid) and cream by using a base Na-CMC 0,25% ; 0,5% and 0,75%. Whereas, optimization of cream base with various concentrations Emulsifying Wax is 10%, 9%, 8%, 7% dan 5%. The results on optimization of lotion base obtained optimal base is base with a concentration of 0,75%, whereas the optimum concentration cream base is 8%. Domestic chicken egg shell’s powder obtained from the process of pollination using a mortar. Cream foundation created in six formulas, namely the first formula containing 5% of active subtance, second formula containing 7,5%, third formula containing 10%, fourth formula containing 12,5%, formula fifth containing 15% and sixth formula containing 17,5%. Stability cream test’s result showed the stocks is stable during 30 days of storage. Having done hedonic test on respondent 52 people based on preference level, obtained result is the first formula become the first order of most preffered with a percentage of 73,5%, second formula at 71,9%, 62,3% for third formula, fourth formula at 57,3%, and fifth formula at 51,2% and sixth formula is 44,6%. Keywords : Foundation, egg shell, cream.